Teamwork barriers and facilitators in the maternity wards: A qualitative study - Seyedeh Tahereh Mirmolaei; Minoor Lamyian; Masoumeh Simbar; Abouali Vedadhir; Aryan Gholipour (Tehran University of Medical Sciences, 2016)
Background & Aim: Teamwork (between obstetricians and midwives) is one of the main pillars of success in the provision of appropriate services in the maternity wards. Therefore, this study aimed to identify the factors influencing teamwork in a maternity ward in a public hospital in Tehran, Iran. Methods & Materials: In this qualitative study, nine midwives and four obstetricians were selected through purposive sampling. Data were collected through semi-structured interviews from an affiliated hospital of Tehran University of Medical Sciences in 2013-2014. Data were analyzed using conventional content analysis. Results: Two themes including the teamwork barriers (four categories) and facilitators (three categories) were extracted from the data analysis. The main categories of teamwork barriers were the underlying issues (inter-professional conflicts, legal issues, and salary and financial issues), individual problems (physical problems, negative personality characteristics and domestic problems), lack of skills (lack of abilities and motivation, educational weakness and lack of experience) and the external management system (inappropriate policy making and planning, hierarchical structure, lack of team evaluation and lack of justice). The main categories of teamwork facilitators were the internal management of team (good leader or manager, appropriate workplace climate, values clarification of the team members' practices, and proper implementation of regulations), cooperation, collaboration and empathy (help and cooperation and empathy and support), and essential personal qualities for teamwork (good communication and good personality characteristics). Conclusion: In this study, the teamwork barriers and facilitators in the maternity wards were comprehensively identified at different levels. According to the results, interventions can be designed and implemented to enhance teamwork.